Combining ultrasound, vacuum and/or ethanol as pretreatments to the convective drying of celery slices - Miano, Alberto Claudio (2021)
This work studied three emerging approaches to improve the convective drying (50 °C, 0.8 m/s) of celery. Celery slices of 2 mm thick were pretreated for 5 min using ultrasound (32 W/L, 40 kHz), vacuum (75 kPa vacuum pressure) and ethanol (99.8% v/v, as drying accelerator) applied individually or in combination. To evaluate individual effects of ultrasound and vacuum, the treatments were also performed with distilled water or air medium, respectively. Moreover, the cavitational level was characterized in each condition. Drying kinetics was evaluated tending into account the drying time required by each treatment and the Page’s model parameters. In addition, microstructural effects and shrinkage were evaluated. As results, ethanol combined with ultrasound significantly improved drying kinetics reducing drying time by around 38%. However, vacuum pretreatment did not affect drying kinetics even in combination with ethanol and/or ultrasound. Microstructural evaluation did not evidence cell disruption, suggesting changes in intercellular spaces, pores and/or cell wall permeability. The use of ethanol and vacuum showed a greater effect on shrinkage after pretreatment and after drying, respectively. In conclusion, at the studied conditions, the drying acceleration by vacuum and ultrasound is lower compared to the effect produced using ethanol.